Providensia Allah di masa Pandemi Covid-19 - Hermanto; Sri Dwi Harti; Charisal B.S. Manu (JURNAL LUXNOS, 2021)
Abstract: The fall of man into sin, brings consequences and rewards that cannot be       denied. In this case, man must bear the yoke of suffering caused by sin. Suffering will      always be in touch wit human life, so that all humans cannot escape suffering. In the       beginning, God made everyhting really very good, but human desires have polluted God’s created world. Thus, human disease and suffering, caused by humans  themselves, include deadly parasites and viruses. However, God never abandons the work of His hands. The purpose of this research it is to remind and strengthen beleivers in particular, to keep standing firm on Jesus Christ who is the steadfast rock. Thus, beleivers are expected to continue to have faith in God’s providence, even in difficult times doe to the pandemic. The research method used is descriptive qualitative, with a library research data collection system through the help of books and related journal  articles. In this study, it was found that even though humans are not faithful, God is still faithful to protect and care for creation. More than that, God through history demonstrated His sovereignty over the universe, namely through His foreknowledge of all things and made all things for His eternal purpose. Abstrak: Kejatuhan manusia kedalam dosa, membawa konsekuensi serta upah yang tidak dapat ditolak. Dalam hal ini, manusia harus memikul kuk penderitaan akibat yang ditimbulkan oleh dosa. Penderitaan akan selalu bersentuhan dengan kehdidupan manusia, sehingga semua manusia tidak dapat luput dari pendertaan. Pada mulanya, Allah menjadikan segala sesuatu sungguh amat baik, tetapi keinginan manusia telah membuat dunia ciptaan Allah menjadi tercemar. Dengan demikian, penyakit serta penderitaan manusia, disebabkan oleh manusia itu sendiri, termasuk parasit serta virus yang mematikan. Meskipun demikian, Allah sekali-kali tidak meninggalkan perbuatan tangan-Nya (providensia). Adapun tujuan dari penelitian ini adalah untuk mengingatkan serta menguatkan orang percaya secara khusus, untuk tetap berdiri teguh pada Yesus Kristus yang adalah batu karang yang teguh itu. Dengan demikian, orang percaya diharapkan tetap beriman pada pemeliharaan Allah, sekalipun di masa sulit akibat Pandemi. Adapun metode penelitian yang digunakan adalah kualitatif deskriptif, dengan sistem pengumpulan data library research melalui bantuan buku-buku serta artikel jurnal yang terkait. Dalam penelitian ini, ditemukan fakta bahwa sekalipun manusia tidak setia, Allah tetap setia untuk menjaga dan memelihara ciptaan. Lebih dari itu, Allah melalui sejarah menunjukkan kedaulatan-Nya atas alam semesta, yakni melalui pra-pengetahuan-Nya atas segala sesuatu dan menjadikan segala sesuatu untuk tujuan kekal-Nya.